2013
DOI: 10.1103/physrevb.88.035431
|View full text |Cite
|
Sign up to set email alerts
|

What x rays can tell us about the interfacial profile of water near hydrophobic surfaces

Abstract: The free surface of water, and the interface between water and a hydrophobic surface, both have positive interface energies. The water density near a free surface drops below the bulk density, and thus it is expected that water near a hydrophobic surface will also show a density depletion.However, efforts by multiple groups to detect and characterize the predicted 'gap' at waterhydrophobic interfaces have produced contradictory results. We have studied the interface between water and fluoroalkylsilane self-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 54 publications
4
73
0
Order By: Relevance
“…This finding indicates that hydrophilic interface produces no surface effect and the interface between the untreated silica and water is indeed hydrophobic. Using specular X-ray reflectivity analysis, Uysal et al [103] confirmed that gap exists between the water the hydrophobic substrate. Therefore, the repelling of the like charges at both the channel and the solid-like drop surfaces governs the observed superfluidity.…”
Section: Dipole Formation and Elastic Enhancementmentioning
confidence: 87%
“…This finding indicates that hydrophilic interface produces no surface effect and the interface between the untreated silica and water is indeed hydrophobic. Using specular X-ray reflectivity analysis, Uysal et al [103] confirmed that gap exists between the water the hydrophobic substrate. Therefore, the repelling of the like charges at both the channel and the solid-like drop surfaces governs the observed superfluidity.…”
Section: Dipole Formation and Elastic Enhancementmentioning
confidence: 87%
“…The thinner of the channel diameter is, the faster the flow rate of the fluid will be [58,59]. An air gap of 0.5-1.0 nm thick exists between the water droplet and the hydrophobic substrates [60]. The gap increases with the contact angle of the droplet.…”
Section: Observationsmentioning
confidence: 99%
“…The air gap between the water and the hydrophobic substrate [16] makes the contacting skin more like free. However, water confined in hydrophilic nanopores [50,51] or wetting with hydrophilic topologic configurations [52] exhibits supercooling effect, or melts at lower temperature than usual because of the lacking of broken bonds.…”
Section: Further Evidencementioning
confidence: 99%
“…Furthermore, the volume of water molecules confined in 5.1 and 2.8 nm TiO 2 pores increase by 4 and 7.5 %, respectively, with respect to that in the bulk [15]. A 5-10 Å thick air gap between water molecules and the hydrophobic surface [16] make water molecules at the interface like free to exhibit skin vibration attributes [17] Stiopkin et al [18] found that the strength of interactions of surface water molecules is distinctly different in structure from the rest of the liquid, and that the water surface has the thickness of just one layer of molecules, which is about 0.3 nm. The surface does not have a long-range impact on water.…”
Section: Ultra-low Density Yet High Elasticitymentioning
confidence: 99%